2007
DOI: 10.1002/cncr.22906
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation beyond 30 grays in 10 fractions for patients with multiple brain metastases

Abstract: BACKGROUND. Whole‐brain radiotherapy (WBRT) to 30 grays (Gy) in 10 fractions is the standard treatment in patients with multiple brain metastases in the majority of treatment centers worldwide. The current study investigated the potential benefit of dose escalation beyond 30 Gy. METHODS. Data regarding 416 patients who were treated with WBRT for multiple brain metastases were evaluated retrospectively. Survival and freedom from recurrent brain metastasis (local control) of 257 patients who were treated with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
1
27
1
1
Order By: Relevance
“…Treatment was highly individualized, taking primary diagnosis, previous therapies and established prognostic factors into consideration [2]. Survival for the different management strategies was within the range of previously reported results [8,9]. This is also true for patients who received systemic chemotherapy (7 months as in the retrospective non-small cell lung cancer study by Kim et al [6] and the subgroup analysis of a prospective phase III trial by Edelman et al [10] in the same cancer type).…”
Section: Discussionsupporting
confidence: 48%
“…Treatment was highly individualized, taking primary diagnosis, previous therapies and established prognostic factors into consideration [2]. Survival for the different management strategies was within the range of previously reported results [8,9]. This is also true for patients who received systemic chemotherapy (7 months as in the retrospective non-small cell lung cancer study by Kim et al [6] and the subgroup analysis of a prospective phase III trial by Edelman et al [10] in the same cancer type).…”
Section: Discussionsupporting
confidence: 48%
“…This topic is controversial in the literature. Certain authors evaluated various radiation schemes and were unable to detect improved survival if patients were treated with a total dose >30 Gy (27)(28)(29). By contrast, two retrospective studies by Mahmoud-Ahmed et al (30) and Meyer et al (31) observed a survival benefit in patients who were treated with a WBRT dose of >30 Gy.…”
Section: P-value -----------------------------------------------mentioning
confidence: 98%
“…Dos diversos esquemas de fracionamento, 30 Gy liberados em 10 frações é o protocolo usual [13]. Doses acima de 30 Gy não aumentam a sobrevida ou controle local de pacientes com múltiplas metástases e frações diárias superiores a 3 Gy podem aumentar o risco de toxicidade [14]. Profilaticamente, a irradiação de cérebro total é utilizada para diminuir a incidência de metástases em indivíduos precocemente diagnosticados com câncer de pulmão de pequenas células ou leucemia linfoblástica aguda.…”
Section: Alscastro; Tprcampos Et Al Scientiaunclassified